2018
DOI: 10.1136/bmjresp-2018-000284
|View full text |Cite
|
Sign up to set email alerts
|

Lung volumes identify an at-risk group in persons with prolonged secondhand tobacco smoke exposure but without overt airflow obstruction

Abstract: IntroductionExposure to secondhand smoke (SHS) is associated with occult obstructive lung disease as evident by abnormal airflow indices representing small airway disease despite having preserved spirometry (normal forced expiratory volume in 1 s-to-forced vital capacity ratio, FEV1/FVC). The significance of lung volumes that reflect air trapping in the presence of preserved spirometry is unclear.MethodsTo investigate whether lung volumes representing air trapping could determine susceptibility to respiratory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Secondhand smoke exposure was another important risk for COPD, and it has been reported that prolonged secondhand smoke exposure can cause increased lung volume without marked airflow limitation. In those at risk for obstruction because of secondhand smoke exposure but with preserved spirometry, higher RV/TLC can identify a subgroup with increased respiratory symptoms and lower exercise capacity . The TLV of the emphysema group was greater than that of the non‐emphysema group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Secondhand smoke exposure was another important risk for COPD, and it has been reported that prolonged secondhand smoke exposure can cause increased lung volume without marked airflow limitation. In those at risk for obstruction because of secondhand smoke exposure but with preserved spirometry, higher RV/TLC can identify a subgroup with increased respiratory symptoms and lower exercise capacity . The TLV of the emphysema group was greater than that of the non‐emphysema group.…”
Section: Discussionmentioning
confidence: 93%
“…CT has been extensively validated as a tool for assessment of the presence, pattern and severity of emphysema . Quantitative CT is currently regarded as an important and complementary method to assess emphysema . However, the normal limit of the EI in the healthy non‐smokers varied from less than 1% to 6.8% in previous studies with different age ranges .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of never-smoking flight crew with history of remote but prolonged exposure to SHS in aircraft cabin, we examined the pulmonary health effects of long-term exposure to SHS and showed the association of those outcomes with the number of years during which the flight crew were exposed to SHS in aircraft cabin. [13][14][15] While this never-smoking SHSexposed cohort had no evidence of spirometric chronic obstructive pulmonary disease (COPD) (a All rights reserved. No reuse allowed without permission.…”
Section: Introductionmentioning
confidence: 99%
“…29.21258054 doi: medRxiv preprint preserved ratio of forced expiratory volume in second to forced vital capacity [FEV1/FVC]), they had abnormal lung function that were suggestive of presence of an occult early/mild obstructive lung disease. 15 In the current study, we wished to examine the cardiovascular health effects of remote but prolonged exposure to SHS in this never-smoking cohort with evidence of early obstructive lung disease. We hypothesized that prolonged exposure to SHS contributes to exercise limitation through its adverse cardiovascular health effects, in addition to its contribution through pulmonary mechanisms (air trapping).…”
Section: Introductionmentioning
confidence: 99%